The Influence of Consumption and Investment on Unemployment in Turkey: a SVAR Approach - Ozan Yıldırım, Mustafa; Eren Yıldırım, Ahmet (Ekonomika, 2017)
The aim of this paper is to examine the dynamic relationship between consumption, investment and unemployment in Turkey using structural VAR (SVAR) models. The four different SVAR models are estimated by using quarterly observations of dynamic and contemporaneous relations for the mentioned macroeconomic variables, covering the 2005-2016 period for the Turkish economy. Four different unemployment rates are used in the study to represent the unemployment rate in the Turkish economy, which are overall, young (15-24 age), male and female unemployment rates. Impulse response functions and variance decomposition results obtained from the study show that consumption shocks have a significant impact on both the unemployment rate and the investments, in support of the basic hypothesis that is argued in the study. Investment shocks also have a similar effect on unemployment rates and positive investment shocks have reduced unemployment rates. Moreover, another result obtained in all four models suggests that a shock in consumption increases investment through the accelerator effect.
Keywords: Consumption; Investment; Unemployment; Structural VAR